COPD discharge bundle and pulmonary rehabilitation referral and uptake following hospitalisation for acute exacerbation of COPD. Issue 8 (2nd March 2021) - Barker, Ruth E; Kon, Samantha SC; Clarke, Stuart F; Wenneberg, Jenni; Nolan, Claire M; Patel, Suhani; Walsh, Jessica A; Polgar, Oliver; Maddocks, Matthew; Farquhar, Morag; Hopkinson, Nicholas S; Bell, Derek; et al.
Abstract : Pulmonary rehabilitation (PR) following hospitalisations for acute exacerbation of COPD (AECOPD) is associated with improved exercise capacity and quality of life, and reduced readmissions. However, referral for, and uptake of, post-hospitalisation PR are low. In this prospective cohort study of 291 consecutive hospitalisations for AECOPD, COPD discharge bundles delivered by PR practitioners compared with non-PR practitioners were associated with increased PR referral (60% vs 12%, p<0.001; adjusted OR: 14.46, 95% CI: 5.28 to 39.57) and uptake (40% vs 32%, p=0.001; adjusted OR: 8.60, 95% CI: 2.51 to 29.50). Closer integration between hospital and PR services may increase post-hospitalisation PR referral and uptake.